2002
DOI: 10.1021/ja0167809
|View full text |Cite
|
Sign up to set email alerts
|

Diazo Group Electrophilicity in Kinamycins and Lomaiviticin A:  Potential Insights into the Molecular Mechanism of Antibacterial and Antitumor Activity

Abstract: Theoretical and chemical studies of the reactivity of isoprekinamycin, the kinamycins, and the lomaiviticins support the proposal that these natural products exhibit enhanced diazonium salt character and may owe their antitumor antibiotic properties to their ability to act as electrophilic azo-coupling agents in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 17 publications
(20 reference statements)
1
43
0
Order By: Relevance
“…In the presence of a cupric acetate oxidant the kinamycin F analog 9-diazofluorene was able to nick DNA [11] which suggests possible oxidative activation. In other prior chemical studies we showed that the diazo group of isoprekinamycin, an analog of kinamycin A, reacted with the nucleophile 2-naphthol, which is known to have good reactivity towards aryldiazonium salts, to yield the azo-coupled product [12]. Collectively these observations led us to the hypothesis that the kinamycins represent variants of the same pharmacophore in which the diazo group, with its diazonium-like character, has unusual biological reactivity and plays a key role in their action as cytotoxic agents.…”
Section: Introductionmentioning
confidence: 97%
“…In the presence of a cupric acetate oxidant the kinamycin F analog 9-diazofluorene was able to nick DNA [11] which suggests possible oxidative activation. In other prior chemical studies we showed that the diazo group of isoprekinamycin, an analog of kinamycin A, reacted with the nucleophile 2-naphthol, which is known to have good reactivity towards aryldiazonium salts, to yield the azo-coupled product [12]. Collectively these observations led us to the hypothesis that the kinamycins represent variants of the same pharmacophore in which the diazo group, with its diazonium-like character, has unusual biological reactivity and plays a key role in their action as cytotoxic agents.…”
Section: Introductionmentioning
confidence: 97%
“…The couplings of arenediazonium ions with thiolates to generate diazosulfides and their decomposition to form aryl radicals are well-known. 35 Although the diazofluorene is formally not an arenediazonium ion, Dmitrienko 30 had shown that this functional group displays enhanced (diazonium-like) electrophilicity. Hydrogen atom abstraction from the deoxy-ribose backbone initiates SSB formation with production of (–)-lomaiviticin C ( 6 ).…”
Section: The Dimeric Diazofluorene Is Required For Potent Cytotoxicitymentioning
confidence: 99%
“…In order to study the molecular mechanism of the antitumor activity of kinamycins [73], Dmitrienko synthesized a structurally simplified analogue of kinamycin involving a Pd-catalyzed C-N bond-forming process. Utilizing the Pd/1 catalyst system, benzylamine was coupled with an aryl bromide to give the secondary amine VIII and debenzylated product IX in a combined 95 % yield.…”
Section: Primary Aliphatic Aminesmentioning
confidence: 99%